Implementasi Marketing Mix Dalam Pemasaran Telur Ayam Ras (Studi Kasus Pada Peternakan Ayam Petelur Mitra Satwa Farm Di Kecamatan Ringinrejo Kabupaten Kediri) - Camal Adi Maskur; Dian Afikasari; Mohamad Ervandi (Jurnal Sains Ternak Tropis, 2026)
Marketing strategy is an important factor in enhancing the competitiveness of layer poultry farming businesses in Kediri Regency. One of the layer poultry farms located in Ringinrejo District, Kediri Regency, is Mitra Satwa Farm. This study aimed to analyze the implementation of the marketing mix in the marketing of chicken eggs at Mitra Satwa Farm. The research employed a qualitative descriptive method using a case study approach. The study was conducted in May 2026. Data were collected through observation, interviews, and documentation involving the business owner, employees, and consumers. Data were analyzed using the stages of data reduction, data presentation, and conclusion drawing. The results showed that the implementation of the marketing mix, consisting of four main elements—product, price, place, and promotion—was categorized as good, with an overall score of 32. The implementation of the product and price elements was categorized as very good, with scores of 9 and 10, respectively. The product strategy emphasized maintaining egg quality, freshness, cleanliness, and size variation, while pricing was determined competitively by considering market prices and production costs. Meanwhile, the place and promotion elements were categorized as less satisfactory, with scores of 6 and 7, respectively. Distribution strategies were implemented through direct sales to consumers, retailers, and business partners, enabling effective market reach. Promotional activities were conducted through direct communication, social media, and customer service. The main challenges encountered included fluctuations in feed prices, market competition, and changes in consumer demand. Overall, the implementation of the marketing mix at Mitra Satwa Farm was effective and contributed positively to improving marketing performance and business competitiveness. Strategi Pemasaran berperan penting dalam meningkatkan daya saing usaha peternakan ayam petelur. Peneltian ini bertujuan menganalisis implementasi bauran pemasaran pada usaha telur ayam ras di Mitra Satwa Farm, Kecamatan Ringin Rejo Kabupaten Kediri. Penelitian ini di laksanakan pada Mei 2026 menggunakan metode kualiattif dengan pendekatan studi kasus. Data diperoleh melalui observasi, wawancara dan dokumentasi kemudian di reduksi data, penyajian data dan panarikan kesimpulan. Hasil penelitian menunjukan bahwa implementasi marketing mix yang meliputi produk, harga, tempat dan promosi termasuk kategori baik dengan skor 32. Aspek Produk dan harga tergolong sangat baik dengan skor masing -masing 9 dan 10, sedangkan aspek tempat dan promosi tergolong kurang baik dengan skor masing-masing 6 dan 7. Pemasaran di lakukan mealui penjulan langsung dan media sosial. kendala utama yang dihadapi meliputi fluktuasi harga pakan, persaingan pasar dan perubahan permintaan. Secara umum implementasi marketing mix berjalan dengan baik dan mendukung pemasaran serta daya saing telur ayam ras.